2016
DOI: 10.17796/1053-4628-40.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Evaluation of the Effectiveness of Formocresol, Mineral Trioxide Aggregate, Portland Cement, and Enamel Matrix Derivative in Primary Teeth Pulpotomies: A Two Year Follow-Up

Abstract: Although there were no statistically significant differences in clinical and radiographic success rates among the 4 groups, MTA appears to be superior to formocresol, Portland cement, and enamel matrix derivative as a pulpotomy agent in primary teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
2
29
0
9
Order By: Relevance
“…Furcation radioluceny and abnormal root resorption were observed as common radiographic findings in formocresol group in the current study. These findings were in accordance with Ibricevic & Qumasha [31] ; Holan et al [32] ; Ruby et al [33] ; Havale et al [34] ; Yildirim et al [35] , they contributing the radiographic changes after Formocresol pulpotomy to different factors such as the possibility of penetration of formaldehyde through the pulpal floor with subsequent damage to the interradicular area.…”
Section: Discussionsupporting
confidence: 88%
“…Furcation radioluceny and abnormal root resorption were observed as common radiographic findings in formocresol group in the current study. These findings were in accordance with Ibricevic & Qumasha [31] ; Holan et al [32] ; Ruby et al [33] ; Havale et al [34] ; Yildirim et al [35] , they contributing the radiographic changes after Formocresol pulpotomy to different factors such as the possibility of penetration of formaldehyde through the pulpal floor with subsequent damage to the interradicular area.…”
Section: Discussionsupporting
confidence: 88%
“…No significant differences in clinical signs and symptoms (presence of pain, sensitivity on percussion and palpation, discoloration, swelling, sinus tract, mobility, lymphadenopathy related to the site of treatment) and radiographic observations (periodontal widening, periapical and furcation radiolucency, external and internal resorption, canal obliteration) were found between enamel matrix derivatives with ProRoot MTA (Yildirim et al . ) as well as diode laser with MTA after pulpotomy in primary molars (Uloopi et al . ).…”
Section: Vital Pulp Therapiesmentioning
confidence: 99%
“…Seven studies [75,79,81,82,84,89,91] reported better clinical outcomes of FC than FS. On the other hand, the comparison between FC and MTA [55,66,67,70,72,[76][77][78]85,86,88,90], yielded a better performance of the latter after 12, 24, 30 and 42 months of evaluation. Accordingly, El Meligy et al [87] observed slightly favorable clinical and radiographical outcomes of primary teeth underwent pulpotomy performed with BD than FC, although no statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The same trend was maintained even after 30 [77] and 42 [78] months of evaluation, respectively. In two additional studies [66,88], it was reported that FC showed slightly worse results than MTA at a 24-month evaluation; however, it performed better than other materials assessed during pulpotomy of primary teeth, such as Pulpotec and Emdogain [88], as well as Portland cement and enamel matrix protein [66]. On the other hand, Jamali et al [65] reported a superiority of MTA in respect to FC after 24 months of evaluation, even though both groups yielded worse results when compared to 3Mixtatin (a combination of simvastatin and 3Mix antibiotic) (78.9% for FC, 90.5% for 3Mixtatin and 88.1% for MTA).…”
Section: Mtamentioning
confidence: 96%